Creation of Humorous Situation By Flouting Conversational Maxims Accompanied By Facial Expression in â€œFriendsâ€ - Faiz Maulida; Fahrur Rozi; Hendi Pratama (English Education Journal, 2022)
This study focused on analyzing the humorous situation created by flouting conversational maxims that were followed by facial expressions found in situated comedy Friends. The analysis included how humorous situation were generated by flouting conversational maxims and the relationship between humorous situation and facial expressions. The results of the study showed that the humorous situations categorized were generated by flouting Grice maxims in which satire and over/understatement were frequently created by means of the implicature from flouting the conversational maxims. In flouting quality, the characters tended not to employ direct lying to other people as it would influence the perspective of the audience about lying to other people as common things although hidden meanings were provided behind the utterances with joy facial expressions. In flouting quantity, the humorous situation was dominated by the creation of overstatement and understatement which were accompanied mostly by joyous facial expression as in line with the definition of overstatement and understatement. In flouting relation, the humorous situation was dominated by satire accompanied by anger facial expressions and clever replies to serious statement accompanied by joyous facial expressions. In flouting manner, satire and pun humorous situation was mostly generated by anger and contempt facial expression. In addition, there were close relationship between certain humorous situation created by flouting conversational maxims and facial expressions. For further study, it is recommended that the study of humorous situation could explore the other aspect of pragmatics elements such as how humor could be generated through the use of politeness strategies within a conversation.